Mobile Technologies for Preservation of Indigenous Knowledge in Rural Communities - Heike, Winschiers-Theophilus; Kasper, Rodil; Tariq, Zaman; Yeo, Alvin Wee (2013)
In this paper we explore the opportunities of mobile technologies in three of our own development endeavors with rural communities, promoting the preservation of indigenous knowledge. We reflect upon and recognize the fact that the representation of indigenous knowledge will be transformed within the digitalization process under the limitations and capabilities of the tools. We believe that a continuation of local appropriation and co-design of tools will lead to an integrated, intuitive and non-intrusive indigenous knowledge preservation process within the local communities.